China's educational cooperation with Africa: toward new strategic partnerships. Issue 1 (20th December 2013) - Niu, Changsong
Abstract : Purpose: – The purpose of this paper is to examine China-Africa educational cooperation under the framework of Forum on China-Africa Cooperation (FOCAC) while illustrating the modalities of Sino-Africa educational cooperation. Design/methodology/approach: – Based on empirical and documentary analysis, the paper describes and explores the unique features of China-Africa educational cooperation. Findings: – In the past decades, China's expanding engagement with Africa in the field of international development assistance has attracted great attention and given rise to mixed reactions and arguments at the international level. China's cooperation with Africa has a long and notable history, dating back to the 1950s. China's cooperation with other developing countries is known as South-South development cooperation, based on principles of equality, mutual benefit, solidarity and no conditionality. With a thorough and critical analysis of the decision-making mechanism and the practices of China's educational cooperation with Africa, this paper puts forward some important issues regarding the perspective of sustainability and effectiveness in Chinese cooperative arrangements. Research limitations/implications: – The paper tries to explain the dynamic and the practices of China's education engagement with Africa and puts forward key challenges regarding its effectiveness toward new strategic partnerships. However, the answers to these questions require some innovative measures in the future practices of China-Africa educational cooperation. Originality/value: – The China-Africa education partnership is not a stand-alone sector, which can be better understood in the context of the historical development of China-Africa cooperation and under the framework of the FOCAC.